EFECTELE APLICĂRII LEGII NR.165/2013 ÎN COMUNA RĂCHITOVA, JUDEŢUL HUNEDOARA (PANGEEA, 2025)
The effects of applying Law No. 165/2013 in Comuna Răchitova, Hunedoara County. Due to inefficiency of the property restitution system in Romania, many of those entitled to restitution of real estate confiscated during the communist period have been issued, for case resolution, to the European authorities, namely the European Court of Human Rights. By pilot-judgment, delivered on 12 October 2010, the ECHR granted Romanian state a period of 18 months in which to fix the refunds issue, in compliance with the Convention. This paper proposes an overview of the measures to complete the restitution process, in kind or compensation, of real estate abusively taken in Romania during the communist regime, accentuating especially the part of land inventory which may be subject to refunds in Răchitova, Hunedoara County.